2016
DOI: 10.3390/ijerph13040430
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity of Graphene–Silver Nanocomposites against Non-Enveloped and Enveloped Viruses

Abstract: The discovery of novel antiviral materials is important because many infectious diseases are caused by viruses. Silver nanoparticles have demonstrated strong antiviral activity, and graphene is a potential antimicrobial material due to its large surface area, high carrier mobility, and biocompatibility. No studies on the antiviral activity of nanomaterials on non-enveloped viruses have been reported. To investigate the antiviral activity of graphene oxide (GO) sheets and GO sheets with silver particles (GO-Ag)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
234
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(236 citation statements)
references
References 28 publications
0
234
0
2
Order By: Relevance
“…), and photocatalysts (TiO 2 , CdS, MnS 2 , etc.) [65]. GO grafted with metal nanoparticles has been investigated as a potential treatment for PPE [66].…”
Section: Antiviral Drug Virus Infection Action Mechanism Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…), and photocatalysts (TiO 2 , CdS, MnS 2 , etc.) [65]. GO grafted with metal nanoparticles has been investigated as a potential treatment for PPE [66].…”
Section: Antiviral Drug Virus Infection Action Mechanism Referencesmentioning
confidence: 99%
“…GO grafted with metal nanoparticles has been investigated as a potential treatment for PPE [66]. Specifically, it is known that silver and copper nano-based systems loaded on GO are very effective against both enveloped and non-enveloped viruses [65,67]. Anti-influenza copper oxide-loaded polypropylene respirators were proposed in 2010; Borkow et al demonstrated that copper oxide-impregnated masks safely reduced the risk of influenza virus environmental contamination, without altering the filtration capabilities of the masks [68].…”
Section: Antiviral Drug Virus Infection Action Mechanism Referencesmentioning
confidence: 99%
“…Overall they concluded that GO in its conjugated form that is GO-AgNPs could inhibit both the virus that is FCoV and IBDV effectively. 131 After diagnosis and therapy the next arising huddle is drug resistance that soon must be focused and acted accordingly. With this intention Li et al, after much evaluations and strategic understanding the drawbacks of conventional and nano-based antiviral, designed nanoparticulated system by decorating amantadine (AM) on surface of selenium NPs (SeNPs).…”
Section: Hybrid Nanoparticlesmentioning
confidence: 99%
“…The reduction of the coronavirus persistence on PPE surfaces can be accomplished by preventing the adhesion of the respiratory droplets onto the material surfaces [ 100 , 101 ]. To this end, metal oxides have been employed on different types of surfaces to induce biocidal effects over pathogens, as it is discussed below [ 65 , 66 , 67 , 69 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 ]. Copper oxide (CuO) is one of the compounds that has been used to design PPE with biocidal properties, such as respiratory face masks [ 67 , 68 , 69 , 114 ].…”
Section: Prevention Of Covid-19 Infection Using Biomedical Sciencementioning
confidence: 99%